Designing an adaptive computer‐aided ambulance dispatch system with Zanshin: an experience report. (11th December 2013) - Silva Souza, Vítor E.; Mylopoulos, John
Summary We have been witnessing growing interest in systems that can adapt their behavior to deal with deviations between their performance and their requirements at run‐time. Such adaptive systems usually need to support some form of a feedback loop that monitors the system's output for problems and carries out adaptation actions when necessary. Being an important feature, adaptivity needs to be considered in early stages of development. Therefore, adopting a requirements engineering perspective, we have proposed an approach and a framework (both called Zanshin) for the engineering of adaptive systems based on a feedback loop architecture. As part of our framework's evaluation, we have applied the Zanshin approach to the design of an adaptive computer‐aided ambulance dispatch system, whose requirements were based on a well‐known case study from the literature. In this paper, we report on the application of Zanshin for the design of an adaptive computer‐aided ambulance dispatch system, presenting elements of the design, as well as the results from simulations of run‐time scenarios. Copyright © 2013 John Wiley & Sons, Ltd.